Graduate Research Abstracts of Post-Occupancy Evaluations Used in Design and Construction: A Bounded Qualitative Meta-Study - Barone, Ryan P.; Banning, James H.; Clemonsc, Stephanie A. (Advances in Social Sciences Research Journal, 2021)
Since its formal introduction in 1967, the concept of post-occupancy evaluation (POE) has been the focus of several substantial books as well as being addressed in key professional journals. In addition, specific POE endeavors related to private and government projects have issued reports of their work. Despite this attention, college and university graduate research work on POEs has not been explored. The purpose of this meta-study using document analysis is to explore the characteristics and implications of college and university graduate POE research focusing on design/construction by analyzing the abstracts of graduate master’s theses and doctoral dissertations that substantially utilized the concept of POE. Results are reported by addressing the characteristics of the research degrees (location/place, type, year, institution, methods associated with the degree, and status of publication) and the characteristics of the research (settings, and focus). The article concludes by calling on the design/construction fields to explore ways to support a greater focus on the communication/coordination and dissemination of international graduate POE research.